2014
DOI: 10.1073/pnas.1407524111
|View full text |Cite
|
Sign up to set email alerts
|

Wild chimpanzees plan their breakfast time, type, and location

Abstract: Not all tropical fruits are equally desired by rainforest foragers and some fruit trees get depleted more quickly and carry fruit for shorter periods than others. We investigated whether a ripe-fruit specialist, the chimpanzee (Pan troglodytes verus), arrived earlier at breakfast sites with very ephemeral and highly sought-after fruit, like figs, than sites with less ephemeral fruit that can be more predictably obtained throughout the entire day. We recorded when and where five adult female chimpanzees spent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 55 publications
5
142
0
2
Order By: Relevance
“…Our pattern of results thus points to a gradual development of this capacity over the middle preschool years. The results also raise the possibility that humans' closest extant relatives lack the capacity altogether, despite being capable of responding flexibly to new risks [22] and possibly solving problems with some foresight [23][24][25]. This would suggest that a new cognitive ability for dealing with environmental uncertainty evolved after the split of the human and chimpanzee lineages approximately 6-8 million years ago [26].…”
Section: Resultsmentioning
confidence: 86%
“…Our pattern of results thus points to a gradual development of this capacity over the middle preschool years. The results also raise the possibility that humans' closest extant relatives lack the capacity altogether, despite being capable of responding flexibly to new risks [22] and possibly solving problems with some foresight [23][24][25]. This would suggest that a new cognitive ability for dealing with environmental uncertainty evolved after the split of the human and chimpanzee lineages approximately 6-8 million years ago [26].…”
Section: Resultsmentioning
confidence: 86%
“…Recent studies reported remarkable spatial memory [43], planning of daily foraging routes [44], and planned short-distance tool transport bouts [45] in the TaĂŻ chimpanzees. In contrast with the time-averaged tool distributions that we report here, these daily activities do not adequately reflect the long-term stone deposition on a landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, would make them more effective seed dispersers, at least for known and favoured sources which would receive rapid seed removal when the fruits are ready to be eaten, decreasing the chances that early fruits would be consumed by seed predators or remain under the parental tree. It is likely to be particularly critical during periods of fruit shortage in the rainforest, such as in months when very few plants carry fruits (Chapman et al 2005;Janmaat et al 2014).…”
Section: Other Aspects Of Memory For Considerationmentioning
confidence: 99%